A Study on Utilization of Rice Husk Ash and Waste Paper Sludge Ash as Partial Replacement of Cement in Concrete (International Journal of Innovative Research in Computer Science & Technology, 2022)
Building with concrete doesn't need any  special skills. Proper proportioning, mixing, and  compacting of the ingredients are essential to concrete's strength. The rising cost of building supplies is a direct  consequence of factors including rising wages, the scarcity  of essential materials, and the skyrocketing cost of  electricity. Consolidating these useful solidifying elements  has several advantages, such as reducing energy  consumption (during cement production), spending less  money, improving design qualities, and protecting the  environment by reducing waste. The physical, synthetic,  and mineralogical qualities of materials, as well as their  piercing power, are all linked to strength. Strength is likely  to benefit from any increase in these qualities. The addition  of a pozzolanic ingredient to a concrete mixture might  significantly enhance the concrete's nature and durability.  There is a common conception of a pozzolanic material,  also known as a pozzolan, as a siliceous and aluminous  substance. In the presence of water and at room  temperature, it undergoes a chemical reaction with lime to  produce compounds with cementitious characteristics.  This happens when the cement mixture is exposed to water  (C-S-H). Several aspects of concrete qualities may be  positively affected by the use of these pozzolanic  materials. The real influences connected to the molecule  size and shape of pozzolans cause the blend extent of  concrete and the rheological behaviour of plastic concrete.  Both the pozzolanic and cementitious processes have a  significant effect on the hardened cement's strength and its  penetrability. Rapid development has usher in an era of  excessive garbage. Most wastes are never put to good use,  and thus contributes to environmental and natural disasters  that don't need the utilisation of extensive fields. There is  evidence that certain of these wastes have great potential  and might be utilised lucratively as a crude blend/mixing  element in cement production. It will help save precious,  rapidly depleting natural resources like limestone. Benefits  to the cement industry include a decrease in the price of  cement production as well as a decrease in the amount of  ozone-depleting substances released per tonne of cement.  As a result, this may also make it easier for cement  businesses to reap the benefits of carbon trading.
Keywords: Rice Husk Ash (RHA); Waste Paper Sludge Ash (WPSA); Compressive Strength